A Method for Stakeholder Mapping in Connection with the Implementation of a Development Project - Katarzyna Styk; Paweł Bogacz (Energies, 2022)
In the case of the energy sector (including mining companies) and the implementation of their development projects, it is necessary to obtain a social license to operate for a given project, which is associated with the involvement of various groups of stakeholders in the project and should be consistent with the company’s strategy. The basis for obtaining permission to operate is to conduct a stakeholder mapping process. Such an analysis will aid effective dialogue with all stakeholders and guide appropriate relationship building. The aim of this paper is to present the authors’ method of stakeholder mapping, which is an independent methodical idea that can be implemented in any enterprise. This paper comprehensively presents this algorithm, starting with the identification of stakeholder groups, through the determination of their level of interest and influence, ending with the construction of a matrix indicating the necessity of undertaking specific communication activities. Finally, the implementation of the created method in the form of a real business project is presented, the advantages are pointed out, and the possibilities and determinants of further development of this algorithm are presented. This method is proposed to companies from the energy sector, including those mining energy resources, as companies that have a significant impact on their social and environmental environment.